The use of dietary supplements in preconception phase of women in Lublin province in the era before the COVID pandemic - Szwed, Monika; Iwaniszyn-Zapołoch, Klara; Żaneta Kimber-Trojnar; Wierzchowska-Opoka, Magdalena; Leszczyńska-Gorzelak, Bożena (Journal of Education, Health and Sport, 2022)
Introduction and purpose Nutrition in the preconception phase as well as during pregnancy represents one of the most important factors that affect the development and well-being of the fetus and newborn. The aim of this study was to evaluate the dietary supplements during preconception among Polish women from the Lublin Province. Material and methods The survey was conducted in a population of 260 women, who were randomly included in the study. The women were asked to anonymously complete a questionnaire regarding the possible intake of supplementation. The questions included in the questionnaire concerned the frequency and type of dietary supplements taken. Results A slight majority of women (53%) did not take dietary supplements during the contraceptive period. The most commonly used was folic acid (45%), the least frequently - vitamin A (2%). The frequency of using dietary supplements by women in the pre-conception period does not correlate with the level of their place of residence, financial situation or age, however, it is related to the level of education - people with higher education used supplementation more often before pregnancy. Women's awareness of supplementation during pregnancy increases significantly. Women take many more supplements during pregnancy than they took before pregnancy. The average supplementation before pregnancy was 0.48, and during pregnancy it increases significantly and amounts to 0.83. Conclusions Women's awareness of supplementation during pregnancy increases significantly. Women take many more supplements during pregnancy than they took before pregnancy.The awareness of women should be increased and supplementation of recommended nutrients should be improved in order to prevent the effects of supplements deficiency.